IL‐22+CD4+ T cells in patients with rheumatoid arthritis. (10th June 2013) - Zhao, Ling; Jiang, Zhenyu; Jiang, Yanfang; Ma, Ning; Zhang, Yandong; Feng, Li; Wang, Kai
Abstract: Aim: Interleukin (IL)‐22 regulates the pathogenesis of autoimmune diseases. The role of IL‐22 + T‐cells in the pathogenesis of rheumatoid arthritis (RA) is unclear. This study aimed at examining the levels of plasma IL‐22 and the frequency of IL‐22 + CD4 + T‐cells in patients with RA. Methods: A total of 30 RA patients and 18 gender‐ and age‐matched healthy controls were recruited. Their peripheral blood mononuclear cells were isolated and stimulated with phorbol 12‐myristate 13‐acetate (PMA) and ionomycin for 6 h. The frequency of IL‐22 +, interferon (IFN)‐γ + and IL‐17A + CD4 + T‐cells was characterized by flow cytometry. The levels of plasma IFN‐γ, IL‐17A and IL‐22, serum C‐reactive protein (CRP), rheumatoid factor (RF), anticyclic citrullinated peptide antibody (CCP) and erythrocyte sedimentation rate (ESR) were measured. Results: The frequency of IFNγ – IL‐17A – IL‐22 +, IFNγ – IL‐17A + IL‐22 +, and IFNγ + IL‐17A – IL‐22 + T‐cells in CD4 + T‐cells and the levels of plasma IFNγ, IL‐17 and IL‐22 in RA patients were significant higher than those in healthy controls. The percentages of IL‐17A + IL‐22 + CD4 + T‐cells were correlated positively with the frequency of Th22 or Th17 cells in the RA patients. The percentages of IL‐22 + CD4 + T‐cells were correlated positively with the values of disease activity score (DAS28) in the RA patients. The percentages of Th22 cells were correlated positively with the levels of plasma IL‐22 in the RA patients. Conclusion: Our data suggest that IL‐22 + CD4 + T‐cells may contribute to the pathogenesis of RA and that therapeutic targeting of IL‐22 may be valuable for the intervention of RA.